A Systematic Review of the Simplex Method in Profit-Oriented Optimization for Manufacturing Industries - Pasaribu, Enita; Hernadewita, Hernadewita; Debora, Fransisca; Attaqwa, Yusita (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
Companies involved in production activities consistently strive to achieve their strategic objectives, with profit maximization being one of the primary goals for maintaining competitiveness and ensuring long-term business sustainability. This goal can be pursued through optimal production planning, one of which involves the application of the Simplex Method (SM). The Simplex Method is a mathematical algorithm designed to solve Linear Programming (LP) problems, which focus on optimizing a linear objective function while accounting for various resource-related constraints. This paper presents a systematic literature review on the implementation of the Simplex Method for profit optimization in the manufacturing sector. A total of 30 relevant research articles published between 2019 and 2024 were analyzed, sourced from reputable academic databases such as Google Scholar and ScienceDirect. The findings demonstrate that the Simplex Method offers substantial benefits, including improved resource allocation, cost reduction, enhanced decision-making capabilities, increased productivity, and support for data-driven operational efficiency. These advantages underscore the method’s effectiveness as a quantitative decision-support tool in strategic industrial planning. The review also highlights the broad applicability of the Simplex Method across various countries and industrial sectors, particularly in food, automotive, chemical, and textile manufacturing. As the manufacturing landscape transitions into the era of Industry 4.0, it is strongly recommended that future research explores the integration of the Simplex Method with emerging technologies such as Big Data analytics, Artificial Intelligence (AI), Cyber-Physical Systems (CPS), and Hybrid Optimization Models to further enhance industrial competitiveness, adaptability, and sustainability.